The Impact of QRIS Policy on the Development of Micro Businesses in Medan City, Indonesia - Arif Rahman; Sukma Hayati Hakim; Wahyu Ario Pratomo (Universitas Hayam Wuruk Perbanas, 2023)
This study analyzes the impact of the QRIS policy in the early stages of implementation on financial performance and expansion of the market share of micro-businesses in Medan City. Financial performance is observed through changes in turnover and net profit; meanwhile, market share is determined based on changes in the number of new customers before and after the implementation of the QRIS policy. This study employs the Difference in Differences (DiD) method. The type of data used is primary data. Purposive and random sampling was utilized with 50 samples of micro businesses for the treatment group and 50 for the control group. The time difference was found between before and after the implementation of the QRIS policy. The results of this study show that the QRIS policy has a positive and significant effect on the increase in new consumers. On the other hand, the QRIS policy has no significant impact on the net profit and turnover of micro businesses. The COVID-19 pandemic has significantly and negatively impacted micro-enterprises, sharply declining revenue and net profit. However, based on the magnitude of the decline, the control group experienced a relatively greater turnover and net profit decline than the treatment group. The implication of this study is the need for efforts to increase micro-entrepreneurs understanding of the importance of faster adaptation to advances in digital technology, one of which is adjustments to a more flexible payment system so that consumers can get a wider choice of payment schemes. In addition, payment system authorities should address various obstacles in using the system and provide more massive socialization of the products offered.